Evaluation of the Effect of Green Energy Policy on Renewable Power Plant Investment in Indonesia - Judijanto, Loso; Jayadi, Harsano; Suryaningsih, Ni Luh Sri; Al Imran, Hamzah (West Science Nature and Technology, 2024)
Indonesia’s transition to renewable energy is a pivotal aspect of its strategy to achieve sustainability and reduce greenhouse gas emissions. This study evaluates the impact of green energy policies on renewable power plant investments in Indonesia through a comparative analysis of solar, wind, geothermal, and hydropower projects. Using data from 2015 to 2024, the study examines the effectiveness of feed-in tariffs, tax incentives, and renewable energy mandates in driving investments. The results show that while policies like feed-in tariffs and tax incentives have significantly boosted investment in geothermal and hydropower projects, solar and wind energy sectors face challenges such as low tariff rates and infrastructure deficits. Comparative insights from successful international cases underscore the need for policy stability, grid expansion, and technology-specific strategies. This research provides actionable recommendations to optimize Indonesia’s green energy framework, fostering a more inclusive and sustainable renewable energy sector.